The Role of Pension Funds in Financing US Federal Debt - P. A. Aksenov; S. V. Emelianov (Управление)
The article examines main trends in financing the federal debt, pointing out its structure, with focus on the role of pension funds as a source of financing; because the surplus of Social Security funds is loaned to the rest of the government; interlinks concerning this process and possible problems; the peculiarities of the federal government pension system’s investment in the government bonds. The US public debt as a share of GDP is much less than in many countries, but its volume is near 20 trln. doll. It may be classified by marketable and non-marketable securities, which are mainly owed to certain government trust funds such as the Social Security trust fund. So the Social Security trust fund, in effect is exchanging one type of debt for the other, taking into consideration that the non-marketable securities represent amounts owed to the beneficiaries. The reserves are in effect borrowed for a time by the rest of the government, and then repaid with interest when the trust funds need them back. Looking ahead Social Security will continue to be financed through its own receipts, mainly payroll tax; and Social Security Trust Fund surplus will become diminishing, with less possibilities to finance federal debt.